Chromatographic analysis of wheatgrass extracts - Masood Shah Khan; Rabea Parveen; Kshipra Mishra; Rajkumar Tulsawani; Sayeed Ahmad (Wolters Kluwer Medknow Publications, 2015)
Aim: Wheatgrass (WG) is the shoot of Triticum aestivum Linn. belongs to the family Gramineae, and possess high chlorophyll content and essential vitamins, minerals, vital enzymes, amino acids, dietary fibers etc., It has been shown to possess anti-cancer, anti-ulcer, antioxidant, and anti-arthritic activity due to the presence of biologically active compounds, and minerals. Therefore, in the present study, high-performance thin layer chromatography (HPTLC), and high-performance liquid chromatography (HPLC) methods for qualitative and quantitative analysis have been proposed, which will help in quality evaluation of wheat grass extract. Materials and Methods: Samples for analysis were prepared in methanol and water simply by sonication. These were applied on pre-coated silica plate and chromatograms were developed using toluene: Ethyl acetate: Formic acid. HPLC analysis was done on Waters HPLC system using water, methanol, and acetonitrile as mobile phase. Merck C18 column has been used. Results: HPTLC finger printing of alcoholic extracts of WG was carried out and found 10-11 spots at different wavelengths 254, 366, and 435 nm. HPLC fingerprinting produced 22 peaks at 256 nm. Quantitative HPTLC analysis was done to determine the gallic acid content, and was found to be 0.077% w/w in aqueous extract. By HPLC, the content of gallic acid and rutin was found to be 0.07%, and 0.04% w/w in aqueous extract of WG. Conclusion: The developed HPLC and HPTLC fingerprinting method can be used for the quality control, and standardization of WG and its extracts used as nutritional supplement.